Strategi Pengembangan Desa Pasrujambe Pasca Ditetapkan Sebagai Desa Wisata di Kabupaten Lumajang - Albhet Raphow Rudolf Cahyono; Nararya Narottama (JURNAL DESTINASI PARIWISATA, 2020)
Reffering to the regulation of the Lumajang Regent number 79 of 2014 about the spread of tourist destinasion, each sub-distric must has a tourism village. So with this regulation Lumajang has 21 tourism village and one of them is Pasrujambe Village. Pasrujambe Village was designated as a tourism village based on the delibration of all village in Pasrujambe Sub-distric, because the village has potentials of tourism like waterfalls, agriculturan land, grebeg nusantara event etc. But now the tourism potentials has not been maximized for tourism activities, so until now Pasrujambe village has not many tourist. The tourism potentials in the village has the oppotunity to be developed to become a tourist activity like something to do, something to see and something to buy. So to achive this develompent requires a strategies based on the avilable potentials and this reasearch does it. The development srategies fromulated iis expected to have an impact such as increased tourist visits, increased local community pasticipation and optimalization tourism potential in the village. The data used in this research are primary and secondary. In this reseacrh observation, interview and literature studies are used to collect data in the reseach location. Descriptive qualiataif and SWOT analysis were used to analyze the data in this research.This research found that potentials of Pasrujambe Village is devided into three categories namely natural-based, culture-based, and artifical human-based. The strategies were devided into four categories are SO strategy with five strategies formulated, WO strategy with four strategies formulated, ST strategy with four strategies formulated, and WT strategy with three strategies formulate. Keywords: Pasrujambe Tourism Village, Tourism Village, Develompmet Strategy